Manufacturing method of magnetic material with self-adaptive electromagnetic compatibility adjusting function

By using magnetic materials with multi-layered gradient composite structures, the technical bottlenecks of traditional electromagnetic compatibility materials in terms of high frequency and wide bandwidth, dynamic response and wide temperature range stability have been solved, realizing adaptive adjustment of electromagnetic interference and meeting the needs of 5G communication and wearable devices.

CN121483853APending Publication Date: 2026-02-06HUBEI UNIV OF AUTOMOTIVE TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511650843.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-12
Publication Date
2026-02-06

AI Technical Summary

Technical Problem

Existing electromagnetic compatibility materials have significant technical bottlenecks in terms of high frequency and wide bandwidth, dynamic response, wide temperature range stability and low power consumption. They cannot adjust the electromagnetic environment in real time, resulting in poor electromagnetic interference suppression and failing to meet the needs of 5G communication and other electronic devices.

Method used

A magnetic material with a multi-layer gradient composite structure, including a matrix layer, a sensing layer, a control layer, and an interface layer, is prepared by processes such as chemical vapor deposition, magnetron sputtering, and atomic layer deposition to construct a sensing-decision-execution closed-loop system, thereby achieving adaptive adjustment to electromagnetic interference.

Benefits of technology

Achieve shielding effectiveness ≥25dB, response time ≤10ns, permeability adjustment range 200-10000, dielectric constant adjustment range 1-1000 within a wide frequency band of 100MHz-40GHz, and stability with permeability fluctuation ≤±5% and shielding effectiveness fluctuation ≤±3dB within the temperature range of -55℃ to 150℃. Reduce power consumption and adapt to the miniaturization requirements of 5G terminals and wearable devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121483853A_ABST
    Figure CN121483853A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of magnetic material manufacturing, and discloses a manufacturing method of a magnetic material with a self-adaptive electromagnetic compatibility regulation function, the material is of a multi-layer gradient composite structure, and the material sequentially comprises a base body layer, a sensing layer, a regulation and control layer and an interface layer from inside to outside; all the layers form a synergistic effect through interface combination, and the matrix layer is formed by compounding soft magnetic alloy powder and a polymer matrix. Compared with the prior art, the manufacturing method of the magnetic material with the self-adaptive electromagnetic compatibility adjustment function systematically solves the core pain points of fixed parameters, response lag, poor wide temperature range performance and complex process of a traditional electromagnetic compatibility material through the innovative design of a multilayer gradient composite structure and a perception-decision-execution closed-loop system; omnibearing breakthrough is achieved in the aspects of dynamic response, broadband adaptability, environment robustness, process compatibility, low power consumption, miniaturization and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of magnetic material manufacturing technology, specifically a method for manufacturing magnetic materials with adaptive electromagnetic compatibility adjustment function. Background Technology

[0002] With the rapid development of 5G communication, the Internet of Things, new energy vehicles, and aerospace technologies, the integration and operating frequency of electronic devices are increasing daily, making electromagnetic interference (EMI) problems increasingly severe. Traditional electromagnetic compatibility materials face significant technical bottlenecks in areas such as high frequency and wide bandwidth (100MHz-40GHz), dynamic response (μs-level delay), wide temperature range stability (-55℃-150℃), and low power consumption requirements.

[0003] The electromagnetic parameters (permeability μ, dielectric constant ε) of existing materials (such as metal alloys, ferrites, and polymer composites) rely on static structural design and cannot be adjusted in real time according to the external electromagnetic environment (such as interference frequency, field strength, and temperature). For example, the permeability of traditional ferrite materials drops sharply in the GHz band (μ < 100), resulting in a high-frequency shielding effectiveness (SE) of less than 10 dB, which is insufficient to meet the requirements of 5G millimeter-wave communication. Materials based on passive adjustment mechanisms (such as conductive polymers and magnetic particle composites) generally have a response time ≥ 1 μs to electromagnetic interference, which cannot match the high-speed signal transmission (ns-level delay requirements) of modern electronic devices. For example, the permeability adjustment of the magnetostrictive material Terfenol-D requires external magnetic field driving, with a response delay of milliseconds, making autonomous dynamic control impossible. The mismatch of the coefficient of thermal expansion (CTE) of traditional materials leads to interlayer delamination (delamination rate ≥ 30%), and the electromagnetic parameters fluctuate significantly at extreme temperatures (-55℃ to 150℃) (permeability fluctuation ± 20%). For example, polyimide-based composite materials are prone to molecular chain relaxation at high temperatures, and their dielectric constant increases non-linearly with increasing temperature, resulting in shielding effectiveness fluctuations exceeding ±5dB. Existing high-performance electromagnetic materials (such as metamaterials and artificial electromagnetic structures) rely on high-precision processes such as electron beam lithography and ion beam sputtering, with production costs reaching as high as $1000 / m². 2 The above, and the yield rate is less than 85%. For example, multilayer metamaterials require multiple photolithographic alignments to achieve gradient structures, with a process cycle of up to 72 hours, which is difficult to meet the needs of large-scale production in consumer electronics; actively modulated materials (such as MEMS switches and phased array antennas) require external power supply (power consumption ≥100mW / cm). 2 Furthermore, the stacked multi-layer structure leads to an increase in volume (thickness ≥ 10 mm). For example, liquid crystal polymer-based tunable materials require integrated driving circuits, increasing the overall system weight by 40%, making it difficult to adapt to the lightweight trend of wearable devices and drones.

[0004] Therefore, we propose a method for fabricating magnetic materials with adaptive electromagnetic compatibility adjustment to address this deficiency in existing technologies. Summary of the Invention

[0005] To address the shortcomings of existing technologies, this invention provides a method for fabricating magnetic materials with adaptive electromagnetic compatibility adjustment capabilities.

[0006] To achieve the above objectives, the present invention provides the following technical solution: a method for fabricating a magnetic material with adaptive electromagnetic compatibility adjustment function, wherein the material is a multi-layer gradient composite structure, comprising, from the inside out, a matrix layer, a sensing layer, a control layer, and an interface layer; each layer forms a synergistic effect through interface bonding, wherein:

[0007] The matrix layer is composed of a soft magnetic alloy powder and a polymer matrix. The soft magnetic alloy powder is selected from one or more of Fe-Si-Al alloy, Fe-Ni-Mo alloy, and Mn-Zn ferrite nanoparticles, with an average particle size of 50-200 nm. The polymer matrix is ​​selected from one of epoxy resin (such as E-51) and polyimide (PI), with a mass ratio of soft magnetic alloy powder to polymer matrix of 8:2-9:1. The thickness of the matrix layer is 0.1-5 mm, and it has an interconnected microporous structure (porosity 5-15 vol%) to enhance the mechanical bonding between the sensing layer and the matrix.

[0008] Sensing layer: A three-dimensional interconnected CNT / graphene heterogeneous network, composed of vertically grown carbon nanotube (CNT) arrays and a substrate graphene film; wherein the graphene film thickness is 0.34-2 nm (monolayer or at least several layers), the CNT diameter is 1-5 nm and the length is 1-10 μm, and the CNT density on the graphene substrate is 102. 8 -10 10 root / cm 2 The sensing layer is grown in situ on the surface of the substrate layer by chemical vapor deposition (CVD), and the bonding strength with the substrate layer is ≥3MPa.

[0009] Control layer: a magnetoelectric coupling functional thin film selected from phase change ceramics (La). 0.7 Sr 0.3 One or more of MnO3-δ, BiFeO3-CoFe2O4, magnetostrictive alloys (Terfenol-D, Ni-Mn-Ga) are used, with a thickness of 5-50 μm; the control layer is deposited on the surface of the sensing layer by magnetron sputtering, and its crystal orientation satisfies the preferential growth of the (111) crystal plane (XRD (111) peak intensity ratio ≥70%).

[0010] Interface layer: A gradient-doped transition metal sulfide film, composed of MoS2 and WS2 in an atomic ratio of 1:1 to 3:1, with a total thickness of 0.5-2 nm. Along the direction from the control layer to the sensing layer, the content of MoS2 gradually changes from 100% to 0% (or the content of WS2 gradually changes from 100% to 0%), forming a Young's modulus gradient (from 100-200 GPa in the control layer to 0.1-1 GPa in the sensing layer). The interface layer is prepared by atomic layer deposition (ALD), and the interlayer interface roughness Ra ≤ 5 nm.

[0011] Furthermore, the surface of the soft magnetic alloy powder in the matrix layer is modified with a coupling agent, which is selected from silane coupling agents KH550 and KH560, and the amount added is 0.1-1 wt% of the mass of the soft magnetic alloy powder; the interfacial bonding energy between the modified powder and the polymer matrix is ​​≥20 mJ / m 2 The tensile strength of the matrix layer is ≥20MPa (≤10MPa when unmodified).

[0012] Furthermore, in the CNT / graphene heterostructure network of the sensing layer, CNTs and graphene are connected through π-π conjugation or van der Waals forces to form a continuous conductive path; its conductivity σ is 10. 3 -10 5 The piezoresistive coefficient (Δρ / ρ / E) is 10 S / cm (at 25℃). -10 -10 -9 Pa -1 The reluctance coefficient (Δρ / ρ / B) is 10. -11 -10 -10 T -1 (B represents the external magnetic field).

[0013] Furthermore, the phase change ceramic of the control layer exhibits a significant abrupt change in electromagnetic parameters near the phase transition temperature (Tc): when the temperature ≥ Tc, La 0.7 Sr 0.3 The resistivity of MnO3-δ ranges from 10 2 Ω·cm drops sharply to 10 -2 Ω·cm (abrupt amplitude ≥ 4 orders of magnitude), dielectric constant ε from 10 2 Jump to 10 4 The magnetic permeability μ of the BiFeO3-CoFe2O4 composite film increased from 2000 to 5000 during the ferroelectric phase transition (an increase of ≥150%).

[0014] Furthermore, the gradient doping structure of the interface layer is achieved by controlling the pulse-purge time of the ALD process: when depositing MoS2, the pulse time of MoF6 is 0.1-0.5s and the reaction time of H2S is 1-3s; when depositing WS2, the pulse time of W(CO)6 is 0.1-0.5s and the reaction time of H2S is 1-3s; by alternately adjusting the number of pulses (5-20 times) of the two precursors, the synergistic control of the thickness gradient and the composition gradient is achieved.

[0015] Furthermore, this includes the following steps:

[0016] Step 1: Pretreatment of the substrate layer

[0017] S1. Raw material mixing: Add the soft magnetic alloy powder and polymer precursor (epoxy resin monomer or polyimide prepolymer) to the ball mill jar at a mass ratio of 8:2-9:1, add 0.1-1wt% of surfactant (silane coupling agent KH550), and ball mill at 200-500rpm for 2-4h to obtain a uniformly dispersed slurry.

[0018] S2. Pre-forming: The slurry is injected into the mold (dimensional accuracy ±5μm) and pre-pressed in a vacuum hot press at 80-120℃ and 5-10MPa to obtain a green body with a thickness of 0.1-5mm; the density of the green body is ≥95% of the theoretical density (tested by Archimedes method).

[0019] Step 2: Preparation of the sensing layer

[0020] S1. Graphene growth: Graphene films (0.34-2 nm thick) are deposited on the surface of a substrate green body using acetylene (C2H2) as the carbon source and Ar / H2 (volume ratio 3:1) as the carrier gas at 500-700℃ via CVD. The reaction pressure is 100-500 Pa and the growth time is 5-15 min.

[0021] S2, CNT array growth: Switch to a methane (CH4) / hydrogen (H2) atmosphere (volume ratio 1:5), using an Fe catalyst (pre-deposited on the substrate surface by magnetron sputtering, 10-50 nm thick) as the catalytic core, grow vertically aligned CNTs (diameter 1-5 nm, length 1-10 μm) at 800-1000℃; reaction pressure 50-200 Pa, growth time 10-30 min;

[0022] S3. Surface modification: Excess CNTs are removed by plasma etching (Ar / O2 mixed gas, power 50-100W, time 30-60s), retaining a CNT density of 10. 8 -10 10 root / cm 2 The sheet resistance of the sensing layer is 10-100Ω / sq.

[0023] Step 3: Deposition of the control layer

[0024] S1. Target material preparation: For phase change ceramic control layers (such as La) 0.7 Sr 0.3 MnO3-δ) was synthesized using a solid-state reaction method to produce coprecipitated targets (purity ≥99.99%) with a particle size ≤5μm; for magnetostrictive alloy control layers (such as Terfenol-D), alloy targets were prepared using a vacuum melting method (Dy / Dy+Tb=0.3, purity ≥99.9%).

[0025] S2. Magnetron sputtering: Depositing a control layer on the surface of the sensing layer, with a vacuum level <5×10⁻⁶. -4 Pa, argon partial pressure 0.3-0.5 Pa, power 100-300 W, sputtering time 30-60 min; the thickness of the control layer is controlled by the combined sputtering power and time (error ≤ ±1 μm);

[0026] S3. Annealing treatment: The deposited sample is placed in a tube furnace and annealed in an oxygen (purity ≥ 99.99%) or nitrogen (purity ≥ 99.99%) atmosphere; the annealing temperature for phase change ceramics is 800-900℃ (La). 0.7 Sr 0.3 MnO3-δ) or 700-800℃ (BiFeO3-CoFe2O4), time 2-4h; the annealing temperature of the magnetostrictive alloy is 400-500℃, time 1-2h; the crystallinity of the annealed sample is ≥90% (XRD half-width ≤0.5°).

[0027] Step 4: Interface Layer Decoration

[0028] S1. ALD Equipment Pretreatment: Place the control layer sample into the ALD reaction chamber and evacuate to <10°C. -3 Pa, heat to 200-300℃ and maintain;

[0029] S2, Gradient Deposition: MoF6 and W(CO)6 precursors are alternately introduced with H2S reaction gas, wherein the pulse time of MoF6 is 0.1-0.5s and the purge time is 10-30s; the pulse time of W(CO)6 is 0.1-0.5s and the purge time is 10-30s; the H2S reaction time is 1-3s and the purge time is 10-30s; by controlling the pulse ratio of MoF6 to W(CO)6 (1:0 to 0:1), gradient doping of MoS2 / WS2 is achieved.

[0030] S3. Post-processing: After deposition, the sample is naturally cooled to room temperature in the ALD cavity. The thickness of the interface layer is precisely controlled by the number of deposition cycles (5-20 cycles) (error ≤ ±0.1nm).

[0031] Step 5: Post-processing and packaging

[0032] S1. Drying treatment: Place the completed multilayer composite material in a vacuum drying oven (60-80℃, vacuum degree <10kPa) and dry for 12-24h to remove residual solvents (such as epoxy resin curing agents).

[0033] S2. Cutting and shaping: The material is cut to the target size (e.g., 10mm×10mm×1mm) using a laser cutting machine (accuracy ±10μm), and the burr height of the cutting edge is ≤5μm;

[0034] S3. Encapsulation treatment: Apply a weather-resistant encapsulating adhesive (such as polyurethane, viscosity 1000-5000 mPa·s) to the material surface, with a coating thickness of 0.1-0.5 mm; place the coated sample in an oven at 80-100℃ for 2-4 hours to cure. The Shore hardness of the encapsulating adhesive after curing is 60-80A.

[0035] Furthermore, during the CVD growth of graphene described in step two, the substrate green body needs to be pre-cleaned with plasma (Ar / O2 mixed gas, power 30-50W, time 10-20s) to remove surface organic contaminants and improve the bonding strength between graphene and the substrate.

[0036] Furthermore, during the magnetron sputtering of the control layer described in step three, the substrate temperature is controlled at 50-150℃ (achieved by heating the back plate), the distance between the target and the substrate is 50-150mm, and the argon flow rate (10-50sccm) is precisely controlled by a mass flow meter during the sputtering process.

[0037] Furthermore, during the ALD deposition of the interface layer in step four, the dew point temperature of the reaction chamber is ≤-40℃ (maintained by a molecular sieve drying system) to avoid water vapor adsorption affecting the film quality; after deposition, the sample needs to be transferred to the subsequent process under the protection of an inert gas (Ar or N2).

[0038] Furthermore, the material exhibits a shielding effectiveness (SE) ≥ 25 dB in the 100 MHz-40 GHz broadband band, a response time ≤ 10 ns to a strong magnetic field (B = 0.5 T), a permeability adjustment range of 200-10000, and a dielectric constant adjustment range of 1-1000; within a temperature range of -55℃ to 150℃, the permeability fluctuation is ≤ ±5%, and the shielding effectiveness fluctuation is ≤ ±3 dB.

[0039] Compared with the prior art, the present invention provides a method for manufacturing magnetic materials with adaptive electromagnetic compatibility adjustment function, which has the following beneficial effects:

[0040] This method for fabricating magnetic materials with adaptive electromagnetic compatibility (EMC) adjustment capabilities systematically addresses the core pain points of traditional EMC materials—namely, fixed parameters, slow response, poor performance over a wide temperature range, and complex manufacturing processes—through an innovative design of a "multi-layer gradient composite structure + sensing-decision-execution closed-loop system." It achieves comprehensive breakthroughs in dynamic response, wideband adaptability, environmental robustness, process compatibility, and low-power miniaturization. The invention constructs a "sensing-decision-execution" closed loop by capturing nanosecond-level signals (response time ≤ 10ns) in the CNT / graphene sensing layer and adjusting the dynamic parameters (phase transition / deformation response ≤ 50ns) in the magnetoelectric coupling control layer. This technology achieves real-time adaptive adjustment of strong electromagnetic interference across a wide bandwidth of 100MHz-40GHz (covering high-frequency scenarios such as 5G millimeter wave and satellite communication) and multiple fields of 0.1V / m-100V / m. The shielding effectiveness (SE) remains stable at ≥25dB ​​across the wide bandwidth (compared to ≤20dB for traditional materials), and the attenuation rate at high frequencies (>10GHz) is only -2dB / decade (compared to -5dB / decade for traditional materials), resulting in a wideband performance improvement of over 100%. This is achieved through stress buffering design of the gradient interface layer (MoS2 / WS2 thin film) (Young's modulus gradient 100-200GPa→0.1-1GPa) and optimization of the thermal stability of phase change materials (such as La). 0.7 Sr 0.3 MnO3-δ annealed crystallinity ≥90% achieves stable performance with permeability fluctuation ≤±5% and SE fluctuation ≤±3dB over a wide temperature range of -55℃ to 150℃ (compared to ≥±20% fluctuation in traditional materials). This makes it reliable for extreme environments such as satellite communication (-55℃ low temperature) and automotive engine compartments (120℃ high temperature). Mature semiconductor processes such as CVD, magnetron sputtering, and ALD (equipment yield ≥98%) replace complex processes like electron beam lithography in traditional metamaterials. Combined with a fault-tolerant gradient interface layer design, it achieves high-consistency mass production with batch-to-batch performance deviation <3% (compared to ≥10% deviation in traditional manual preparation), meeting the large-scale manufacturing needs of 5G mobile phone PCBs and automotive motor production lines. Through a self-powered mechanism (CNT / graphene electromagnetic induction + piezoelectric effect, self-powered efficiency 0.5μW / cm²), it achieves a high-consistency mass production with batch-to-batch performance deviation <3% (compared to ≥10% deviation in traditional manual preparation). 2 The multi-layered composite structure (total thickness ≤ 5mm) overcomes the limitation of traditional active adjustment materials requiring an external power source (power consumption ≥ 100mW / cm²). 2 Furthermore, due to the limitation of large thickness (≥10mm), the working energy consumption is <1mW / cm. 2 (Reduced by two orders of magnitude), with a volume and weight reduction of more than 60%, making it suitable for miniaturized scenarios such as 5G terminals and wearable devices. Attached Figure Description

[0041] Figure 1 This is a schematic diagram of a multilayer gradient composite structure for a magnetic material fabrication method with adaptive electromagnetic compatibility adjustment function proposed in this invention.

[0042] Figure 2 This is a schematic diagram of the fabrication process of the magnetic material fabrication method with adaptive electromagnetic compatibility adjustment function proposed in this invention.

[0043] Figure 3 The present invention presents a comparison curve of shielding effectiveness with that of traditional Fe-Si-Al ferrite. Detailed Implementation

[0044] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0045] Please see Figure 1-3 A method for fabricating magnetic materials with adaptive electromagnetic compatibility adjustment capabilities is disclosed. The material has a multi-layered gradient composite structure, comprising, from the inside out, a matrix layer, a sensing layer, a control layer, and an interface layer. Each layer works synergistically through interface bonding.

[0046] The matrix layer is composed of a soft magnetic alloy powder and a polymer matrix. The soft magnetic alloy powder is selected from one or more of Fe-Si-Al alloy, Fe-Ni-Mo alloy, and Mn-Zn ferrite nanoparticles, with an average particle size of 50-200 nm. The polymer matrix is ​​selected from one of epoxy resin (such as E-51) and polyimide (PI), with a mass ratio of soft magnetic alloy powder to polymer matrix of 8:2-9:1. The thickness of the matrix layer is 0.1-5 mm, and it has an interconnected microporous structure (porosity 5-15 vol%) to enhance the mechanical bonding between the sensing layer and the matrix.

[0047] Sensing layer: A three-dimensional interconnected CNT / graphene heterogeneous network, composed of vertically grown carbon nanotube (CNT) arrays and a substrate graphene film; wherein the graphene film thickness is 0.34-2 nm (monolayer or at least several layers), the CNT diameter is 1-5 nm and the length is 1-10 μm, and the CNT density on the graphene substrate is 102. 8 -10 10 root / cm 2 The sensing layer is grown in situ on the surface of the substrate layer by chemical vapor deposition (CVD), and the bonding strength with the substrate layer is ≥3MPa.

[0048] Control layer: a magnetoelectric coupling functional thin film selected from phase change ceramics (La). 0.7 Sr 0.3One or more of MnO3-δ, BiFeO3-CoFe2O4, magnetostrictive alloys (Terfenol-D, Ni-Mn-Ga) are used, with a thickness of 5-50 μm; the control layer is deposited on the surface of the sensing layer by magnetron sputtering, and its crystal orientation satisfies the preferential growth of the (111) crystal plane (XRD (111) peak intensity ratio ≥70%).

[0049] Interface layer: A gradient-doped transition metal sulfide film, composed of MoS2 and WS2 in an atomic ratio of 1:1 to 3:1, with a total thickness of 0.5-2 nm. Along the direction from the control layer to the sensing layer, the content of MoS2 gradually changes from 100% to 0% (or the content of WS2 gradually changes from 100% to 0%), forming a Young's modulus gradient (from 100-200 GPa in the control layer to 0.1-1 GPa in the sensing layer). The interface layer is prepared by atomic layer deposition (ALD), and the interlayer interface roughness Ra ≤ 5 nm. The multilayer composite structure achieves adaptive adjustment of electromagnetic interference across a wide bandwidth (100MHz-40GHz) and multiple field strengths (0.1V / m-100V / m) through electromagnetic signal sensing in the sensing layer (CNT / graphene), dynamic parameter adjustment in the control layer (magnetoelectric coupling material), and low-stress synergy in the interface layer. The shielding effectiveness (SE) is improved by ≥50% compared to traditional materials (conventional materials SE≤20dB, this invention SE≥25dB).

[0050] The soft magnetic alloy powder in the matrix layer is modified with a coupling agent, selected from silane coupling agents KH550 and KH560, at a dosage of 0.1-1 wt% of the soft magnetic alloy powder mass. The interfacial bonding energy between the modified powder and the polymer matrix is ​​≥20 mJ / m. 2 The tensile strength of the matrix layer is ≥20MPa (≤10MPa without modification). This modified design enhances the mechanical bonding between the matrix layer and the sensing layer, avoids interlayer delamination in multilayer composites (the delamination rate of traditional materials is ≥30%, while that of this invention is <5%), and improves the reliability of the material under vibration / impact scenarios.

[0051] In the CNT / graphene heterostructure of the sensing layer, CNTs and graphene are connected through π-π conjugation or van der Waals forces to form a continuous conductive pathway; its conductivity σ is 10. 3 -10 5 The piezoresistive coefficient (Δρ / ρ / E) is 10 S / cm (at 25℃). -10 -10 -9 Pa -1 The reluctance coefficient (Δρ / ρ / B) is 10. -11 -10 -10 T -1(B represents the applied magnetic field). This highly conductive network can quickly sense changes in induced current or stress induced by electromagnetic interference (response time ≤ 10 ns), providing precise "sensing-decision" signal input to the control layer and solving the problem of hysteresis (≥ 1 μs) in traditional materials.

[0052] Among them, the phase change ceramic of the control layer exhibits a significant abrupt change in electromagnetic parameters near the phase change temperature (Tc): when the temperature ≥ Tc, La 0.7 Sr 0.3 The resistivity of MnO3-δ ranges from 10 2 Ω·cm drops sharply to 10 -2 Ω·cm (abrupt amplitude ≥ 4 orders of magnitude), dielectric constant ε from 10 2 Jump to 10 4 The magnetic permeability μ of the BiFeO3-CoFe2O4 composite film increases from 2000 to 5000 during the ferroelectric phase transition (an increase of ≥150%). This phase transition characteristic allows the control layer to dynamically adjust the material's equivalent electromagnetic parameters (μ adjustment range 200-10000, ε adjustment range 1-1000), achieving efficient suppression of high-frequency (>1GHz) electromagnetic interference (conventional materials have a high-frequency SE <10dB, while this invention has an SE ≥28dB).

[0053] The gradient doping structure of the interface layer is achieved through pulse-purge time control in the ALD process: when depositing MoS2, the pulse time for MoF6 is 0.1-0.5 s, and the reaction time for H2S is 1-3 s; when depositing WS2, the pulse time for W(CO)6 is 0.1-0.5 s, and the reaction time for H2S is 1-3 s. By alternating the number of pulses for the two precursors (5-20 times), the thickness gradient and composition gradient are synergistically controlled. This gradient design effectively alleviates interlayer thermal stress (CTE mismatch), and the material exhibits an interlayer peeling rate of <5% after 100 cycles from -55℃ to 150℃ (compared to ≥30% for conventional materials), achieving performance stability over a wide temperature range (-55℃-150℃) (permeability fluctuation ≤±5%, SE fluctuation ≤±3dB).

[0054] The method for fabricating magnetic materials with adaptive electromagnetic compatibility adjustment function includes the following steps:

[0055] Step 1: Pretreatment of the substrate layer

[0056] S1. Raw material mixing: Add the soft magnetic alloy powder and polymer precursor (epoxy resin monomer or polyimide prepolymer) to the ball mill jar at a mass ratio of 8:2-9:1, add 0.1-1wt% of surfactant (silane coupling agent KH550), and ball mill at 200-500rpm for 2-4h to obtain a uniformly dispersed slurry.

[0057] S2. Pre-forming: The slurry is injected into the mold (dimensional accuracy ±5μm) and pre-pressed in a vacuum hot press at 80-120℃ and 5-10MPa to obtain a green matrix with a thickness of 0.1-5mm; the density of the green matrix is ​​≥95% of the theoretical density (tested by Archimedes method); the matrix layer pretreatment improves the mechanical strength of the matrix and the bonding force of the sensing layer through powder modification and microporous structure design, providing a stable support substrate for subsequent multilayer composites.

[0058] Step 2: Preparation of the sensing layer

[0059] S1. Graphene growth: Graphene films (0.34-2 nm thick) are deposited on the surface of a substrate green body using acetylene (C2H2) as the carbon source and Ar / H2 (volume ratio 3:1) as the carrier gas at 500-700℃ via CVD. The reaction pressure is 100-500 Pa and the growth time is 5-15 min.

[0060] S2, CNT array growth: Switch to a methane (CH4) / hydrogen (H2) atmosphere (volume ratio 1:5), using an Fe catalyst (pre-deposited on the substrate surface by magnetron sputtering, 10-50 nm thick) as the catalytic core, grow vertically aligned CNTs (diameter 1-5 nm, length 1-10 μm) at 800-1000℃; reaction pressure 50-200 Pa, growth time 10-30 min;

[0061] S3. Surface modification: Excess CNTs are removed by plasma etching (Ar / O2 mixed gas, power 50-100W, time 30-60s), retaining a CNT density of 10. 8 -10 10 root / cm 2 The sheet resistance of the sensing layer is 10-100 Ω / sq. The sensing layer was fabricated using CVD in-situ growth technology to construct a highly conductive three-dimensional CNT / graphene network. Its fast response characteristics (≤10ns) provide a "neural sensing" function for the adaptive regulation of the material.

[0062] Step 3: Deposition of the control layer

[0063] S1. Target material preparation: For phase change ceramic control layers (such as La) 0.7 Sr 0.3 MnO3-δ) was synthesized using a solid-state reaction method to produce coprecipitated targets (purity ≥99.99%) with a particle size ≤5μm; for magnetostrictive alloy control layers (such as Terfenol-D), alloy targets were prepared using a vacuum melting method (Dy / Dy+Tb=0.3, purity ≥99.9%).

[0064] S2. Magnetron sputtering: Depositing a control layer on the surface of the sensing layer, with a vacuum level <5×10⁻⁶.-4 Pa, argon partial pressure 0.3-0.5 Pa, power 100-300 W, sputtering time 30-60 min; the thickness of the control layer is controlled by the combined sputtering power and time (error ≤ ±1 μm);

[0065] S3. Annealing treatment: The deposited sample is placed in a tube furnace and annealed in an oxygen (purity ≥ 99.99%) or nitrogen (purity ≥ 99.99%) atmosphere; the annealing temperature for phase change ceramics is 800-900℃ (La). 0.7 Sr 0.3 MnO3-δ) or 700-800℃ (BiFeO3-CoFe2O4), time 2-4h; the annealing temperature of the magnetostrictive alloy is 400-500℃, time 1-2h; the crystallinity of the annealed sample is ≥90% (XRD half-width ≤0.5°); the control layer deposition optimizes the crystallinity and phase transition characteristics of the film through magnetron sputtering and annealing processes, ensuring that it can quickly undergo electromagnetic parameter mutations under electromagnetic interference (response time ≤50ns), realizing closed-loop control of "decision-execution".

[0066] Step 4: Interface Layer Decoration

[0067] S1. ALD Equipment Pretreatment: Place the control layer sample into the ALD reaction chamber and evacuate to <10°C. -3 P a Heat to 200-300℃ and maintain;

[0068] S2, Gradient Deposition: MoF6 and W(CO)6 precursors are alternately introduced with H2S reaction gas, wherein the pulse time of MoF6 is 0.1-0.5s and the purge time is 10-30s; the pulse time of W(CO)6 is 0.1-0.5s and the purge time is 10-30s; the H2S reaction time is 1-3s and the purge time is 10-30s; by controlling the pulse ratio of MoF6 to W(CO)6 (1:0 to 0:1), gradient doping of MoS2 / WS2 is achieved.

[0069] S3. Post-processing: After deposition, the sample is naturally cooled to room temperature in the ALD chamber. The thickness of the interface layer is precisely controlled by the number of deposition cycles (5-20 cycles) (error ≤ ±0.1nm). The interface layer modification, through the precise control of the ALD process, constructs a low stress gradient interface, which solves the problem of interlayer delamination caused by the mismatch of thermal expansion coefficients in multilayer materials (traditional delamination rate ≥30%, this invention <5%), and improves the reliability of the material in a wide temperature range.

[0070] Step 5: Post-processing and packaging

[0071] S1. Drying treatment: Place the completed multilayer composite material in a vacuum drying oven (60-80℃, vacuum degree <10kPa) and dry for 12-24h to remove residual solvents (such as epoxy resin curing agents).

[0072] S2. Cutting and shaping: The material is cut to the target size (e.g., 10mm×10mm×1mm) using a laser cutting machine (accuracy ±10μm), and the burr height of the cutting edge is ≤5μm;

[0073] S3. Encapsulation: Apply a weather-resistant encapsulating adhesive (such as polyurethane, viscosity 1000-5000 mPa·s) to the material surface, with a coating thickness of 0.1-0.5 mm; place the coated sample in an oven at 80-100℃ for 2-4 hours to cure. The Shore hardness of the encapsulating adhesive after curing is 60-80A. The post-processing and encapsulation process, through drying, cutting, and weather-resistant encapsulation, ensures the dimensional accuracy and long-term stability of the material (weather resistance ≥ 5 years), meeting the industrial application needs of scenarios such as 5G communication and new energy vehicles.

[0074] In step two, during the CVD growth of graphene, the substrate preform needs to undergo plasma cleaning (Ar / O2 mixed gas, power 30-50W, time 10-20s) to remove surface organic contaminants and improve the bonding strength between graphene and the substrate. This cleaning step removes surface organic contaminants and improves the bonding strength between graphene and the substrate (binding energy ≥20mJ / m). 2 This avoids interlayer delamination during multilayer composite processes.

[0075] In step three, during the magnetron sputtering of the control layer, the substrate temperature is controlled at 50-150℃ (achieved by heating the back plate), the distance between the target and the substrate is 50-150mm, and the argon flow rate (10-50sccm) is precisely controlled by a mass flow meter during sputtering. These process parameters optimize the crystallization uniformity of the control layer (grain size uniformity ≥95%) and ensure the consistency of electromagnetic parameter adjustment (batch deviation <3%).

[0076] In step four, during the ALD deposition of the interface layer, the dew point temperature of the reaction chamber is ≤-40℃ (maintained by a molecular sieve drying system) to avoid water vapor adsorption affecting the film quality. After deposition, the sample needs to be transferred to the subsequent process under the protection of inert gas (Ar or N2). This measure avoids the influence of water vapor adsorption on the film quality (interface roughness Ra≤5nm) and improves the low stress synergistic effect of the interface layer.

[0077] Specifically, the material has a shielding effectiveness (SE) ≥ 25 dB in the 100 MHz-40 GHz broadband band, a response time ≤ 10 ns to a strong magnetic field (B = 0.5 T), a permeability adjustment range of 200-10000, and a dielectric constant adjustment range of 1-1000; in the temperature range of -55℃ to 150℃, the permeability fluctuation is ≤ ±5%, and the shielding effectiveness fluctuation is ≤ ±3 dB.

[0078] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A method for manufacturing a magnetic material with adaptive electromagnetic compatibility adjustment function, characterized in that, The material is a multi-layer gradient composite structure, which comprises a substrate layer, a sensing layer, a regulation layer and an interface layer from inside to outside; each layer is combined through the interface to form a synergistic effect, wherein: The substrate layer is composed of soft magnetic alloy powder and polymer matrix, the soft magnetic alloy powder is selected from one or more of Fe-Si-Al alloy, Fe-Ni-Mo alloy and Mn-Zn ferrite nanoparticles, the average particle size is 50-200 nm; the polymer matrix is selected from one of epoxy resin (such as E-51) and polyimide (PI), the mass ratio of soft magnetic alloy powder to polymer matrix is 8:2-9:1; the thickness of the substrate layer is 0.1-5 mm, and the inside has a connected microporous structure (porosity 5-15 vol%), which is used to enhance the mechanical bonding force between the sensing layer and the substrate; The sensing layer is a three-dimensional interconnected CNT / graphene heterogeneous network, which is composed of a vertical growth carbon nanotube (CNT) array and a substrate graphene film; wherein the graphene film has a thickness of 0.34-2 nm (at least several layers of a single layer), the CNT has a diameter of 1-5 nm and a length of 1-10 μm, and the density of the CNT on the graphene substrate is 10 8 -10 10 root / cm 2 ; the sensing layer is grown in situ on the surface of the substrate layer by a chemical vapor deposition (CVD) method, and the bonding strength with the substrate layer is greater than or equal to 3 MPa. The regulation layer is a magnetoelectric coupling functional film, which is selected from one or more of phase change ceramics (La0.7Sr0.3MnO3-δ, BiFeO3-CoFe2O4) and magnetostrictive alloy (Terfenol-D, Ni-Mn-Ga), and the thickness is 5-50 μm; the regulation layer is deposited on the surface of the sensing layer by magnetron sputtering method, and the crystal orientation meets the condition that the (111) crystal surface grows preferentially (XRD (111) peak intensity ratio ≥ 70%); The interface layer is a gradient-doped transition metal sulfide film, which is composed of MoS2 and WS2 with an atomic ratio of 1:1-3:1, and the total thickness is 0.5-2 nm; along the direction from the regulation layer to the sensing layer, the content of MoS2 gradually changes from 100% to 0% (or the content of WS2 gradually changes from 100% to 0%), forming a Young's modulus gradient (from 100-200 GPa of the regulation layer to 0.1-1 GPa of the sensing layer); the interface layer is prepared by atomic layer deposition (ALD) method, and the interfacial roughness Ra is ≤5 nm.

2. The method of claim 1, wherein the method further comprises: The surface of the soft magnetic alloy powder of the base layer is modified by a coupling agent, the modifier is selected from one of silane coupling agents KH550 and KH560, and the addition amount is 0.1-1wt% of the mass of the soft magnetic alloy powder; the interfacial bonding energy of the modified powder and the polymer matrix is ≥20mJ / m 2 , and the tensile strength of the base layer is ≥20MPa (≤10MPa when unmodified).

3. The method of claim 1, wherein the method further comprises: In the CNT / graphene heterogeneous network of the sensing layer, CNT and graphene are connected through π-π conjugation effect or Van der Waals force to form a continuous conductive path; the conductivity σ thereof is 10 3 -10 5 S / cm (at 25℃), the piezoresistive coefficient (Δρ / ρ / E) is 10 -10 -10 -9 Pa -1 , the magneto-resistive coefficient (Δρ / ρ / B) is 10 -11 -10 -10 T-1 (B is an applied magnetic field).

4. The method of claim 1, wherein the method further comprises: The phase change ceramic of the control layer presents a significant electromagnetic parameter mutation near the phase change temperature (Tc): when the temperature ≥ Tc, the resistivity of La0.7Sr0.3MnO3-δ suddenly drops from 10 2 Ω·cm to 10-2Ω·cm (mutation amplitude ≥ 4 orders of magnitude), the dielectric constant ε jumps from 10 2 4 ; the magnetic permeability μ of the BiFeO3-CoFe2O4 composite film increases from 2000 to 5000 (amplitude of increase ≥ 150%) at the ferroelectric phase change.​ 5. The method of claim 1, wherein the method further comprises: The gradient-doped structure of the interface layer is realized by pulse-sweep time control of the ALD process: when depositing MoS2, the MoF6 pulse time is 0.1-0.5 s, and the H2S reaction time is 1-3 s; when depositing WS2, the W(CO)6 pulse time is 0.1-0.5 s, and the H2S reaction time is 1-3 s; by alternately adjusting the pulse number of the two precursors (5-20 times), the thickness gradient and the composition gradient are synergistically controlled.

6. The method of claim 1-5, wherein the method further comprises: The method comprises the following steps: Step one: substrate layer pretreatment S1, raw material mixing: add the soft magnetic alloy powder and the polymer precursor (epoxy resin monomer or polyimide prepolymer) into the ball mill tank according to the mass ratio of 8:2-9:1, add 0.1-1 wt% of a surfactant (silane coupling agent KH550), and ball mill at a speed of 200-500 rpm for 2-4 h to obtain a uniformly dispersed slurry; S2, preforming: inject the slurry into a mold (dimensional accuracy ±5 μm), and preform in a vacuum hot press at 80-120 ℃ and 5-10 MPa to obtain a substrate green body with a thickness of 0.1-5 mm; the density of the green body is ≥95% of the theoretical density (tested by the Archimedes method). Step two: sensing layer preparation S1, graphene growth: graphene thin film (thickness 0.34-2 nm) was deposited on the surface of the green body by CVD method, using acetylene (C2H2) as carbon source and Ar / H2 (volume ratio 3:1) as carrier gas at 500-700℃; the reaction pressure was 100-500 Pa and the growth time was 5-15 min; S2, CNT array growth: the CNT (diameter 1-5 nm, length 1-10 μm) was grown vertically by switching to methane (CH4) / hydrogen (H2) (volume ratio 1:5) atmosphere and using Fe catalyst (previously deposited on the surface of the green body by magnetron sputtering, thickness 10-50 nm) as catalytic core at 800-1000℃; the reaction pressure was 50-200 Pa and the growth time was 10-30 min; S3, surface modification: remove excess CNTs by plasma etching (Ar / O2 mixed gas, power 50-100 W, time 30-60 s) to retain CNT density of 10 8 -10 10 Roots / cm 2 , and the sheet resistance of the sensing layer is 10-100 Ω / sq. Step three: deposition of the regulation layer S1, target preparation: for the phase change ceramic regulation layer (such as La0.7Sr0.3MnO3-δ), the co-precipitation target (purity ≥99.99%) was synthesized by solid phase reaction method, and the particle size was ≤5 μm; for the magnetostrictive alloy regulation layer (such as Terfenol-D), the alloy target (Dy / Dy+Tb=0.3, purity ≥99.9%) was prepared by vacuum melting method; S2, magnetron sputtering: depositing the regulation layer on the surface of the sensing layer, vacuum degree < 5 x 10 -4 Pa, argon partial pressure 0.3-0.5 Pa, power 100-300 W, sputtering time 30-60 min; the thickness of the regulation layer is controlled by the sputtering power and time (error ≤ ± 1 μm); S3, annealing: the sample after deposition is placed in a tube furnace, annealed in oxygen (purity≥99.99%) or nitrogen (purity≥99.99%) atmosphere; the annealing temperature of phase change ceramics is 800-900℃ (La 0.7 Sr 0.3 MnO3-δ) or 700-800℃ (BiFeO3-CoFe2O4), for 2-4h; the annealing temperature of magnetostrictive alloy is 400-500℃, for 1-2h; the crystallinity of sample after annealing is≥90% (XRD half-peak width≤0.5°). Step four: interface layer modification S1, ALD equipment pretreatment: Put the sample into the ALD reaction cavity, vacuumize to < 10-3Pa a Heating to 200-300°C and keeping; S2, gradient deposition: MoF6, W(CO)6 precursors and H2S reaction gas were alternately introduced, wherein the pulse time of MoF6 was 0.1-0.5 s and the purge time was 10-30 s; the pulse time of W(CO)6 was 0.1-0.5 s and the purge time was 10-30 s; the reaction time of H2S was 1-3 s and the purge time was 10-30 s; by controlling the pulse number ratio of MoF6 to W(CO)6 (1:0 to 0:1), the gradient doping of MoS2 / WS2 was realized; S3, post-processing: after the deposition was completed, the sample was naturally cooled to room temperature in the ALD chamber, and the thickness of the interface layer was accurately controlled (error ≤±0.1 nm) by the number of deposition cycles (5-20 cycles). Step five: post-processing and packaging S1, drying treatment: the material after the completion of the multilayer composite was placed in a vacuum drying box (60-80℃, vacuum degree <10 kPa) for 12-24 h to remove the residual solvent (such as epoxy resin curing agent); S2, cutting and forming: the material was cut into the target size (such as 10 mm×10 mm×1 mm) by a laser cutting machine (accuracy ±10 μm), and the height of the cutting edge burr was ≤5 μm; S3, packaging treatment: a weather-resistant packaging glue (such as polyurethane, viscosity 1000-5000 mPa·s) was coated on the surface of the material, and the coating thickness was 0.1-0.5 mm; the sample coated with glue was placed in an oven at 80-100℃ for 2-4 h, and the Shore hardness of the cured packaging glue was 60-80A.

7. The method of claim 6, wherein the method further comprises: In step two, the green body should be pre-plasma cleaned (Ar / O2 mixed gas, power 30-50 W, time 10-20 s) to remove surface organic contaminants and improve the bonding strength of graphene and the green body.

8. The method of claim 6, wherein the method further comprises: In the step three, the substrate temperature is controlled at 50-150℃ (achieved by heating back plate), the distance between target and substrate is 50-150mm, and the argon flow rate is controlled by mass flow meter (10-50sccm) during sputtering.

9. The method of claim 6, wherein the method further comprises: In the step four, the dew point temperature of the reaction cavity is ≤-40℃ (maintained by molecular sieve drying system) to avoid water vapor adsorption affecting the film quality; after deposition, the sample needs to be transferred to the subsequent process under the protection of inert gas (Ar or N2). ​ 10. The method of claim 1-5, wherein the method further comprises: The material has a shielding effectiveness (SE) ≥25dB in a wide frequency band of 100MHz-40GHz, a response time ≤10ns to a strong magnetic field (B=0.5T), a magnetic permeability adjustment range of 200-10000, a dielectric constant adjustment range of 1-1000, a magnetic permeability fluctuation ≤±5% in a temperature range of-55℃ to 150℃, and a shielding effectiveness fluctuation ≤±3dB. ​